2021
DOI: 10.1016/j.ihj.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

ADDition of DAPAgliflozin, Sodium-Glucose Cotransporter-2 Inhibitor to Angiotensin Receptor Blocker-Neprilysin Inhibitors Non-Responders in Patient with Refractory Heart Failure with Reduced Ejection Fraction (ADD DAPA trial)

Abstract: Objectives We evaluated the efficacy and safety of dapagliflozin, a SGLT2i along with ARNI in refractory HFrEF irrespective of their diabetic status. Methods We performed a retrospective analysis of 104 symptomatic patients of HFrEF despite of optimal medical management with ARNI between January–June 2020. Despite the optimal GDMT, dapagliflozin, SGLT2i was added inpatients withrefractory heart failure. At 6-months follow-up, the primary outcome was change in left ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
2
0
2
Order By: Relevance
“…These findings are consistent with a study 15 which evaluated the effect of dapagliflozin in HF with mildly reduced EF. Similar effects of dapagliflzoin were stated by another study 16 which observed a significant improvement in NYHA class with the addition of 10mg dapagliflozin to standard therapy for refractory HF patients.…”
Section: Discussionsupporting
confidence: 79%
“…These findings are consistent with a study 15 which evaluated the effect of dapagliflozin in HF with mildly reduced EF. Similar effects of dapagliflzoin were stated by another study 16 which observed a significant improvement in NYHA class with the addition of 10mg dapagliflozin to standard therapy for refractory HF patients.…”
Section: Discussionsupporting
confidence: 79%
“…Assim, demonstra-se que o seu uso está associado a um aumento significativo na sobrevida de pacientes com coração congestivo. O estudo "Dapagliflozin in patients with heart failure and reduced ejection fraction (DAPA-HF)", publicado em 2020, demonstrou que a dapagliflozina adicionada ao tratamento padrão versus o tratamento padrão sozinho promoveu diminuição considerável no risco de hospitalização por IC e na mortalidade cardiovascular em pacientes com ICFEr (JARIWALA et al, 2021).…”
Section: Resultsunclassified
“…Regarding the effect of dapagliflozin on the LVEF, there have been conflicting results. In the ADD DAPA study (ADDition of DAPAgliflozin, Sodium–Glucose Cotransporter-2 Inhibitor to Angiotensin Receptor Blocker-Neprilysin Inhibitors Non-Responders in Patient with Refractory Heart Failure with Reduced Ejection Fraction), a retrospective analysis of 104 patients with HFrEF, dapagliflozin administration for 6 months was found to improve the LVEF [(29 ± 4% to 38 ± 5%; +9.00 ± 0.628%; p < 0.001)] [ 35 ]. In contrast, in the REFORM study, dapagliflozin administration for 12 months had no effect on the LVEF [ 14 ].…”
Section: Discussionmentioning
confidence: 99%